Pakatan Rakyat turns defensive over its blunders beleaguered: Backlash in trying to politicise every issue - Ariff, Syed Umar (New Straits Times, 2013)
THE opposition pact has found itself seething in criticism of late, from brickbats hurled against their populist manifesto to accusations that alluded them to be involved in the Lahad Datu standoff. For the past two weeks, Pakatan Rakyat's head honcho and supposedly its prime minister candidate Datuk Seri Anwar Ibrahim had been on the defensive in his nationwide ceramah rounds, as noted by political observers.